LONTAR GAMA TIRTHA; PEMULIAAN AIR DALAM KONTEKS EKO-RELIGIUS - I Gede Sudiarta; Reland Udayana Tangkas (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Lontar Gama Tirtha is one of the Balinese literatures which has been inherited until now by Balinese people who believe in the position of water as a means of self-purification. Water has a very important position in the ecological system and is able to form ecosystems in the area of lakes, rivers, rice fields, and springs that are not only useful for daily needs but are also highly purified and functioned spiritually. Lontar Gama Tirtha explains the essence of water as a means of self-purification and a system of knowledge of water that is integrated with human beings. Lontar Gama Tirtha thoroughly explains the two water belief contexts that refer to the physical and spiritual aspects, namely